Environmental performance, carbon performance and earnings management: Empirical evidence for the European capital market - Patrick Velte (Corporate Social Responsibility and Environmental Management, 2021)
The purpose of this study is to examine the relationship between environmental performance, carbon performance and earnings management. This analysis includes panel regressions as empirical-quantitative (archival) research methods and looks at the 2014–2018 financial years of companies listed on the STOXX Europe 600 (1,509 firm-year observations). Environmental (carbon) performance proxies are included as independent variables, and with two earnings quality measures, accrual-based earnings management (ACC) and real earnings management (REM) as dependent variables. Our findings align with prior research on sustainability performance and indicate that environmental (carbon) performance reduces ACC but increases REM. After including Granger causality tests, we find no indications of a bidirectional relationship. This analysis makes a key contribution to prior studies as this appears to be the first on the relationship between environmental (carbon) performance and earnings management in the European capital market. The study has major implications for business practice, regulators and research. Managers might use environmental and carbon strategies for greenwashing policies as this change in earnings management can be hardly detected by other stakeholders.
Keywords: 650; carbon performance; corporate governance; earnings management; earnings quality; environmental performance